The migrant worker: visible, yet invisible. (22nd January 2015) - Win, Aung
Abstract : Immigrant workers are a vulnerable and underserved population. The average life expectancy of the migrant worker is 49 years, compared to 77.2 years for most Americans. Immigrant workers have a higher disease burden than other populations and work in occupations with high hazard levels. In addition, they have low socioeconomic levels and face many barriers to accessing healthcare services. Undocumented immigrant workers are excluded in the Affordable Care Act. Health professionals must be attuned to the health issues of new immigrants so that they can provide better services. In order to raise the health standards of America, health professionals must provide healthcare for all, including immigrant workers.